2016
DOI: 10.1002/cnm.2780
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of non‐Newtonian blood models within a heart pump

Abstract: A detailed computational fluid dynamics (CFD) study of transient, turbulent blood flow through a positive displacement left ventricular assist device is performed. Two common models for non-Newtonian blood flow are compared to the Newtonian model to investigate their impact on predicted levels of shear rate and wall shear stress. Given that both parameters are directly relevant to the evaluation of risk from thrombus and haemolysis, there is a need to assess the sensitivity to modelling non-Newtonian flow effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In general, the non-Newtonian properties of blood are only apparent at shear rates less than 100 s -1 [3]. However, experimental and numerical models have shown that non-Newtonian behavior has a significant influence in the microvasculature [4] and in a variety of settings where low-shear flow is more prevalent such as in ventricular assist devices and aneuryms [5,6,28]. For example, a laser Doppler velocimetry analysis of flow in a pediatric ventricular assist device demonstrated that using a Newtonian fluid generally overestimated wall shear stress and therefore underestimated areas of low wall shear stress/thrombogenic potential compared to a non-Newtonian fluid [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the non-Newtonian properties of blood are only apparent at shear rates less than 100 s -1 [3]. However, experimental and numerical models have shown that non-Newtonian behavior has a significant influence in the microvasculature [4] and in a variety of settings where low-shear flow is more prevalent such as in ventricular assist devices and aneuryms [5,6,28]. For example, a laser Doppler velocimetry analysis of flow in a pediatric ventricular assist device demonstrated that using a Newtonian fluid generally overestimated wall shear stress and therefore underestimated areas of low wall shear stress/thrombogenic potential compared to a non-Newtonian fluid [5].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a laser Doppler velocimetry analysis of flow in a pediatric ventricular assist device demonstrated that using a Newtonian fluid generally overestimated wall shear stress and therefore underestimated areas of low wall shear stress/thrombogenic potential compared to a non-Newtonian fluid [5]. A more recent computational fluid dynamics simulation comparing a Newtonian model with two non-Newtonian models in a similar ventricular assist device showed increased turbulent kinetic energy and a larger area of flow recirculation in the non-Newtonian models [6]. Interestingly, in contrast to the Bachmann study the predicted wall shear stress was similar between the Newtonian and non-Newtonian models; this is potentially explained by the larger size of the device in the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of computational fluid dynamics (CFD) overcomes the mentioned complications and provides a cost‐effective approach to analyze these devices. Many researchers have utilized the CFD techniques to simulate the blood pump and they found the computational findings are in good agreement with their experimental results. This shows that CFD can be a reliable approach to analyze the blood pumps under different operating conditions with lesser complications, as faced in equivalent experiments.…”
Section: Introductionmentioning
confidence: 73%
“…Hemocompatibility has remained a big area of interest. One recent study looked at the degradation of von Willebrand factor (VWF) in continuous flow LVAD and determined that turbulence remained an important factor in VWF degradation regardless of exposure time with the device [22].…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%